2013
DOI: 10.1002/jmri.24525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity on T1 and T2* relaxation times of healthy achilles tendons at 3T

Abstract: Prolonged T2* values especially in the mid-portion of the Achilles tendon of runners are likely to reflect an adaptation of the tendon microstructure to repetitive tendon straining activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
24
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
(79 reference statements)
9
24
2
Order By: Relevance
“…34 Several studies have been performed assessing relaxation times of healthy and degenerated tendons in vivo and in vitro using T2* with short echo-times. 9,13,33,[35][36][37][38][39][40] Our results in healthy bovine tendons are comparable to T1 and T2* values of a recent ex vivo 34 and in vivo studies, 33,36 with T2* values ranging from 0.92 to 2.72 milliseconds and T1 values ranging from 311 to 733 milliseconds.…”
Section: Discussionsupporting
confidence: 88%
“…34 Several studies have been performed assessing relaxation times of healthy and degenerated tendons in vivo and in vitro using T2* with short echo-times. 9,13,33,[35][36][37][38][39][40] Our results in healthy bovine tendons are comparable to T1 and T2* values of a recent ex vivo 34 and in vivo studies, 33,36 with T2* values ranging from 0.92 to 2.72 milliseconds and T1 values ranging from 311 to 733 milliseconds.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to earlier reports, the presented study focuses on the time course of various MR‐specific parameters after ankle‐straining activity, to further analyze the hydration state, i.e., changes in the free water content of the Achilles tendon (Grosse et al., ). Please note, that all of these MR‐specific parameters and the semi‐automatic tendon volume assessment have already demonstrated an excellent reproducibility in previous studies (coefficient of variation of OSR measurements at the mid‐portion tendon area: 1.6%; coefficient of variation of tendon volume measurements: 1.2%), and that OSR as well as T2* measurements in this study are within the range of previously reported values for the mid‐portion Achilles tendon area (Syha et al., , , , ; Grosse et al., , , ). In addition, it is worth noting that contrary to earlier studies in this work only OSR values of the mid‐portion tendon area (which is deemed to be the most stressed part of the Achilles tendon during cross‐country) were analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…Ultrashort echo time (UTE) based MRI methods have been used to capture average T2 * relaxation time of the Achilles tendon (mid-portion, insertion region, muscle-tendon junction, and whole Achilles tendon-aponeurosis) in a group of recreational long distance runners compared to healthy volunteers, showing longer T2 * relaxation times in the mid-portion and whole Achilles tendon-aponeurosis for runners ( Grosse et al, 2015 ). Longer T2 * relaxation times are believed to reflect a greater amount of free water protons between collagen fibres, reduced collagen alignment, and have previously been reported to distinguish between healthy and pathological Achilles tendons ( Juras et al, 2012 , 2013 ; Gärdin et al, 2016 ; Qiao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%